2022
DOI: 10.21203/rs.3.rs-1403603/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pivotal Role of miRNA-21 in Myocardial Metabolic Flexibility in Response to Short- and Long-term High Glucose Treatment: Evidence in Human Cardiomyocyte Cell Line

Abstract: BackgroundmiRNA-21 is a micro-RNA widely studied for its implications in several biological functions, including apoptosis, inflammation, fibrosis, and metabolism. Interestingly, miRNA-21 is a crucial regulator of developing cardiac diseases, but its role is controversial, and it is necessary to clarify its function in pathophysiological events of diabetic cardiomyopathy. In the present study we clarified the protective role of miRNA-21 at cardiac level and evaluated the involvement of miRNA-21 in high glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Using the principles and technologies of bioinformatics to process the genes, transcriptomics, proteomics, drugs, biological networks and other items of various tissue samples of cardiovascular diseases for data mining and analysis, which can provide effective data support for pathological mechanism research, early diagnosis, drug mechanism of action, etc. Existing studies have proved that metabolomics, lipidomics and proteomics comparative analysis of human cardiomyocytes treated with high glucose concentration or empagliflozin treatment have very effectively revealed that empagliflozin treatment improves the phenomenon of high glucose-induced cellular stress (14). Guo et al verified by linking bioinformatics analysis and molecular biology experiments to verify that transcription factor Tcea3 affects cardiac remodeling by participating in fatty acid oxidation, ATP synthesis, and mitochondrial oxidative stress.…”
Section: Novel Bioinformatics Analysis Of Transcription Regulation In...mentioning
confidence: 99%
“…Using the principles and technologies of bioinformatics to process the genes, transcriptomics, proteomics, drugs, biological networks and other items of various tissue samples of cardiovascular diseases for data mining and analysis, which can provide effective data support for pathological mechanism research, early diagnosis, drug mechanism of action, etc. Existing studies have proved that metabolomics, lipidomics and proteomics comparative analysis of human cardiomyocytes treated with high glucose concentration or empagliflozin treatment have very effectively revealed that empagliflozin treatment improves the phenomenon of high glucose-induced cellular stress (14). Guo et al verified by linking bioinformatics analysis and molecular biology experiments to verify that transcription factor Tcea3 affects cardiac remodeling by participating in fatty acid oxidation, ATP synthesis, and mitochondrial oxidative stress.…”
Section: Novel Bioinformatics Analysis Of Transcription Regulation In...mentioning
confidence: 99%